Investigating self-cooling effects of ventilated attics under different roof and ambient temperatures in summer - Shen, Zhigang; Wang, Shimin (Journal of Civil Engineering and Management, 2014)
An unsteady computational fluid dynamics model is employed to simulate summer-time buoyancy-driven turbulent ventilation in gable-roof attics of residential buildings. The energy performance of vented attics is assessed by comparing their performance to sealed attics with the same geometry and insulation configurations. The simulated boundary conditions of the roof-top temperature ranging between 295.15 K and 345.15 K, coupled with an ambient temperature ranging between 295.15 K and 315.15 K, resemble the summer attic conditions with effects of solar irradiance on the roofs. Simulation results indicate that both the vented and sealed attics are dominated by thermal stratification. The cooling load of the sealed attic is predicted to be about 3 times greater than that of the vented attic for a roof-top temperature of 345.15 K and an ambient temperature of 305.15 K. Both the cooling load and ventilating air flow rate of the vented attic are sensitive to the ambient temperature variation.